Study on the provision of vitamin a and exclusive breastfeeding with the growth of toddlers - Setyowati, Susana; sayuti, Sayuti; Qotimah, Qotimah; Rokhamah, Rokhamah; Adelia, Donna Dwinita (Institute Of Computer Science (IOCS), 2025)
Growth is the increase in the size and number of cells and intracellular tissues, meaning the increase in physical size and structure of the body in part or in whole, so that it can be measured in units of length and weight. This period is a period that occurs quickly and will not be repeated, therefore it is often called the golden age. One thing that is related to growth is the provision of vitamin A and the provision of exclusive breastfeeding. This study uses a quantitative method with a cross-sectional approach with a sample of mothers who have toddlers in Lawak Village, Ngimbang District, Lamongan Regency, totaling 30 mothers. The results of this study obtained the F count value (128.091) > F0.05 (3.35) meaning that there is a significant influence between the variables of vitamin A provision and exclusive breastfeeding with toddler growth in weight. The F count value (123.225) > F0.05 (3.35) meaning that there is a significant influence between the variables of vitamin A provision and exclusive breastfeeding with toddler growth in height. So it can be concluded that there is a relationship between vitamin A provision and exclusive breastfeeding with toddler growth in weight and height.